2021
DOI: 10.12968/denu.2021.48.7.524
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable oral healthcare and the environment: mitigation strategies

Abstract: Carbon emissions and single-use plastics (SUPs) are the main forms of environmental pollution relating to waste arising from oral healthcare. Ownership of this problem is shared with the whole supply chain, from manufacturing to distribution, procurement, clinical use and finally, waste management. Mitigation strategies focus on the individual stakeholders in the supply chain, including the provision of clinical care. Key to this is establishing a baseline analysis of the nature and the size of the problem thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Education is considered as the fundamental component of any remediation strategy, with a focus on increasing awareness and identifying remediation solutions for each sector and for the supply chain as a whole 14,15 . Effective education programmes should include communication, dissemination and participation at all levels 16,17 .…”
Section: Sustainability Awareness Through Educationmentioning
confidence: 99%
“…Education is considered as the fundamental component of any remediation strategy, with a focus on increasing awareness and identifying remediation solutions for each sector and for the supply chain as a whole 14,15 . Effective education programmes should include communication, dissemination and participation at all levels 16,17 .…”
Section: Sustainability Awareness Through Educationmentioning
confidence: 99%
“…End-users are generally considered to be poorly engaged in sustainable practices, but this is not quantified. There is a need to change behaviour at home and at the workplace [8,32]. Within this low level of awareness in the oral healthcare sector, there is a wide range between different challenges in different world regions, each with its own specific challenges.…”
Section: Stakeholdersmentioning
confidence: 99%
“…The additional PPE required during the COVID-19 pandemic increased this figure to approximately 2.4 billion SUP items (27 tonnes) in the UK. Further studies of this type are required in alternative settings to obtain a clear baseline and to help inform remediation strategies [32,38,45]. Recycling as a basis for a business model is a significant challenge that needs resolving.…”
Section: Awareness and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…These all add a considerable environmental impact that should not be ignored but is outside the scope of this paper. 8,9 The aim of this report is to provide a comprehensive review of the potential pollutant risk to the environment from the chemical compounds found in resin-based restorative materials, by considering: 1) the principal pollutant compounds present in the resin matrix; 2) the degradation process of RBCs and its consequences; 3) the methods used for the detection and quantification of monomer eluants and microparticles; and 4) a review of the release mechanisms of eluants and microparticles into the environment.…”
Section: Introductionmentioning
confidence: 99%